2015
DOI: 10.3389/fimmu.2015.00147
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelium Interactions with Aeroallergens: Role of Secreted Cytokines and Chemokines in Innate Immunity

Abstract: Airway epithelial cells are the first line of defense against the constituents of the inhaled air, which include allergens, pathogens, pollutants, and toxic compounds. The epithelium not only prevents the penetration of these foreign substances into the interstitium, but also senses their presence and informs the organism’s immune system of the impending assault. The epithelium accomplishes the latter through the release of inflammatory cytokines and chemokines that recruit and activate innate immune cells at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 165 publications
(195 reference statements)
0
75
0
2
Order By: Relevance
“…Previous studies have shown that exposure to HDM can trigger allergic inflammation in asthmatic patients12829. Components of HDM, including Der p1, Der p3 and Der p9 exhibit proteolytic activity that leads to activation of PAR2 receptors, which in turn plays a critical role in mediating the inflammatory effects of HDM830.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that exposure to HDM can trigger allergic inflammation in asthmatic patients12829. Components of HDM, including Der p1, Der p3 and Der p9 exhibit proteolytic activity that leads to activation of PAR2 receptors, which in turn plays a critical role in mediating the inflammatory effects of HDM830.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we found that CNC is most similar to chitin while NCF responses were mostly parallel to CNF. It has been previously reported that chitin induces robust innate immune responses (Gandhi and Vliagoftis, 2015), while CNF are known to be cytotoxic and genotoxic (Kisin et al, 2011;Murray et al, 2012). Importantly, it has been reported that exposure to chitin can result in innate allergic inflammation characterized by alternatively activated macrophages and eosinophilia in vivo (Kogiso et al, 2011;Reese et al, 2007;Van Dyken et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the airway epithelium by allergens and other environmental factors can lead to the release of mediators, which affect airway smooth muscle cells. Studies have shown that the airway epithelium modulates smooth muscle cell proliferation by secreting interleukin-6 (IL-6), IL-8 and monocyte chemotactic protein-1 (MCP-1) which are known mitogens of ASM cells [35,36]. Human ASM cells have also been shown to secrete MCP-1, which attracts monocytes and lymphocytes and stimulate the release of histamine from basophils, when stimulated with tumor necrosis factor alpha (TNF-α) and IL-1β [37].…”
Section: Airway Smooth Muscle Cells In Asthma Pathogenesismentioning
confidence: 99%